Pengembangan Sistem Monitoring Suhu dan Kelembaban di Ruang Fermentasi Tembakau Bawah Naungan (TBN) Berbasis Internet of Things (IoT) - Andrew Setiawan Rusdianto; Lia Milata Khasanah; Bertung Suryadharma; Yuli Wibowo; Nidya Shara Mahardika (JOFE : Journal of Food Engineering, 2022)
Fermentation is one of the processes in tobacco processing which will be used as raw material for cigars. One of the main aspects that must be considered to achieve successful fermentation is the temperature and humidity of the fermentation room, namely 60-80% RH and 27-32 °C. KOPA Tarutama Nusantara (TTN) Jember is a Under Shade Tobacco processing unit with manual monitoring of temperature and humidity using a hygrometer which causes workers to experience fatigue and delays in taking action if the temperature and humidity are not up to standard. Based on these problems, an IoT (Internet of Things)-based temperature and humidity monitoring tool is needed. The research was carried out by assembling tools using Arduino Ide, DHT 11 Sensor, 2 Channel Relay, LM2596 and programmed with Arduino Ide software. Based on the functionality validation test, this tool can be said to function properly because the X value is 1. The efficiency value is declared very efficient with a value 6.9% and the effectiveness value is declared very effective because the effectiveness value increases from 17 to 22. The implementation of this tools in the fermentation room also increases the effectiveness of tobacco quality with a value of 112.9%.